Analisis Pengaruh Nilai Perilaku dan Kepribadian terhadap Motivasi Kinerja Mitra Driver Gojek di Kota Medan - Emi Angelina Sinambela; Dina Lestari; Salsa Zuhriana Nasution; Yohana Dwi Simaremare; Lokot Muda Harahap (JURNAL RISET MANAJEMEN (JURMA), 2025)
This study aims to analyze the influence of behavioral values and personality on the performance motivation of Gojek partner drivers in Medan City. The growth of application-based transportation services requires driver performance that is shaped not only by external organizational factors but also by internal characteristics inherent to each individual. Using a descriptive qualitative approach through a literature-based review, this study examines how behavioral values such as honesty, discipline, responsibility, and work ethics strengthen drivers’ commitment and consistency in delivering services. Furthermore, personality traits including emotional stability, perseverance, friendliness, and adaptability are found to significantly contribute to drivers’ ability to manage work pressure and maintain high-quality interactions with customers. The analysis reveals that strong behavioral values foster intrinsic motivation that enhances job performance, while positive work behavior and stable personality traits reinforce extrinsic motivation through customer satisfaction and improved ratings. Overall, behavioral values, work behavior, and personality are interrelated and collectively shape the performance motivation of partner drivers. These findings highlight the importance of character development, behavioral training, and personal competency enhancement to sustainably improve the quality of application-based transportation services.